Biopolymeric formulations for filtrate control applications in water-based drilling muds: A review - Ali, I. (Elsevier B.V., 2022)
The forthcoming future of environmental protection mandates the utilization of naturally abundant, biodegradable, sustainable and ecofriendly materials for a wide variety of applications. Fluid loss behavior is considered the most severe problem in oil and gas well drilling operations. Because several other issues are associated with it. As a working way out, viscosifiers and fluid loss additives are introduced to the mud for rheology and filtration characteristics improvements, respectively. Polymers and starches are commonly added to base fluid to increase viscosity and reduce fluid loss of a mud. In this paper, the utilization of biopolymers used in the drilling fluid industry for filtrate reduction has been addressed. This review further emphasizes on the recent developments in native and modified starches utilization in drilling fluids extracted from various sources and the present research gaps for future developments. The utilization of biopolymers as potential additive in nondamaging water-based muds have been addressed to reduce the impacts of mud filtrate in the exposed formations. Moreover, various factors that influence the effectiveness of biopolymers and the utilization of such polymers in different muds are also discussed. The filtration characteristics in terms of filtrate volume and filtercake thickness generally showed improvements by using biopolymers. Filtercakes generated from starch-containing muds have been found to be thinner and more compact, resulting in reduced formation damage due to lower mud particle penetration. Â© 2021 Elsevier B.V.